Psychological Antecedents of the Intention to Open the Windows at Home and Exposure to a Ventilation Recommendation - Durand, François; Bonnefoy, Barbara; Marchand, Dorothée; Meyer, Thierry (Frontiers in Psychology, 2022)
Objective: The psychological antecedents of the intention to open the windows at home were explored through the Theory of Planned Behavior (TPB), supplemented with Habits regarding the behavior and contextual factors. Design: A four-treatment design compared the effect of an exposure to a recommendation about home ventilation and the effect of one’s own awareness odors (negative vs. positive) as a manipulated variable. Two quasi-experimental online surveys were conducted. A student sample (Study 1; N=158) was replicated with a general population sample (Study 2; N = 350). Results: Multiple hierarchical regression models were conducted (3 for Study 1; 4 for Study 2). The extended TPB model provided stable predictors explaining around sixty percent of variance. Attitude and Habits were the main predictors of window opening, Perceived Behavioral control as a secondary predictor. Perceived Behavioral Control contributed significatively with a negative interaction with Attitudes. Odor awareness decreased Intention to manually ventilate. No effect of recommendation was observed. Discussion: The results filled a gap in the literature about the willingness to manually ventilate at home and efficacy of a recommendation. Practical implications argue that beyond a generic recommendation, effective messages need to be tailored regarding the determinants of willingness to open the windows.